Determination of Motivation, Competence and Training on Employee Performance Throught Job Satisfaction - Salju; Gatotrianto B; Andi Nadirah (International Journal of Economics (IJEC), 2024)
This study aims to determine the effect of motivation, competence and training on employee performance with job satisfaction as an intervening variable at the Department of Agriculture and Food, East Luwu Regency. The sample was selected using the slovin formula and a total of 130 samples were obtained. The data used with a quantitative approach. The analysis used inferential statistics with structural equation modeling (SEM) techniques based on variance (VB). The analysis tool used is SMART PLS 3.0. The results showed: (1) Employee performance is positively and not significantly influenced by motivation, while competence and training positively and significantly affect performance. (2) Job satisfaction is positively and significantly influenced by motivation, competency and training. (3) Job satisfaction serves as an intervening variable that has a positive and significant effect on motivation, competence and training on employee performance. Therefore, this research can also be used by local governments, especially in the East Luwu Regency Region, as reference material on improving employee performance through job satisfaction by increasing work motivation, increasing competency and increasing employee job training.